PEMBERIAN LAYANAN BIMBINGAN PRIBADI SOSIAL DALAM MENINGKATKAN DISIPLIN GURU TERHADAP KETIDAK HADIRAN MENGAJAR DI KELAS PADA UPT SD NEGERI 060875 TEGAL REJO KECAMATAN MEDAN PERJUANGAN - Pasaribu, Ida Suryani (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of this study is to find out: How to improve teacher discipline in teaching in the classroom through the provision of personal guidance services to UPT SD Negeri 060875, Medan Perjuangan sub-district. This research was conducted using classroom action research by applying trials in two cycles. Cycle I personal social guidance services that have not reached the amount of 55%. In other words, personal social guidance services in improving teacher discipline in teaching attendance in class have increased 100%. In this second cycle, personal guidance services that have not achieved teacher discipline in class teaching attendance are 55%. In other words, personal social guidance services achieve 100% success.